Bile acid homeostasis in female mice deficient in Cyp7a1 and Cyp27a1 - Daniel Rizzolo; Bo Kong; Rulaiha E. Taylor; Anita Brinker; Michael Goedken; Brian Buckley; Grace L. Guo (Elsevier, 2021)
Bile acids (BAs) are amphipathic molecules important for metabolism of cholesterol, absorption of lipids and lipid soluble vitamins, bile flow, and regulation of gut microbiome. There are over 30 different BA species known to exist in humans and mice, which are endogenous modulators of at least 6 different membrane or nuclear receptors. This diversity of ligands and receptors play important roles in health and disease; however, the full functions of each individual BA in vivo remain unclear. We generated a mouse model lacking the initiating enzymes, CYP7A1 and CYP27A1, in the two main pathways of BA synthesis. Because females are more susceptible to BA related diseases, such as intrahepatic cholestasis of pregnancy, we expanded this model into female mice. The null mice of Cyp7a1 and Cyp27a1 were crossbred to create double knockout (DKO) mice. BA concentrations in female DKO mice had reductions in serum (63%), liver (83%), gallbladder (94%), and small intestine (85%), as compared to WT mice. Despite low BA levels, DKO mice had a similar expression pattern to that of WT mice for genes involved in BA regulation, synthesis, conjugation, and transport. Additionally, through treatment with a synthetic FXR agonist, GW4064, female DKO mice responded to FXR activation similarly to WT mice.